2022
DOI: 10.1128/msphere.00283-22
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Evaluation of a Rapid Fully Automated Analysis Platform to Detect and Refute Outbreaks Based on MRSA Genome Comparisons

Abstract: It has been clearly established that genome sequencing of MRSA improves the accuracy of health care-associated outbreak investigations, including the confirmation and exclusion of outbreaks and identification of patients involved. This could lead to more targeted infection control actions but its use in clinical practice is prevented by several barriers, one of which is the availability of genome analysis tools that do not depend on specialist knowledge to analyze or interpret the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Genome analysis was performed using the automated NGD cloud-based bioinformatics system, as previously described [ 6 8 ]. In brief, on completion of the sequencing run this system uploaded raw fastq folders via an encrypted secure upload to the Amazon UK Web Services cloud, where 60 compute nodes were automatically activated.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Genome analysis was performed using the automated NGD cloud-based bioinformatics system, as previously described [ 6 8 ]. In brief, on completion of the sequencing run this system uploaded raw fastq folders via an encrypted secure upload to the Amazon UK Web Services cloud, where 60 compute nodes were automatically activated.…”
Section: Methodsmentioning
confidence: 99%
“…A second study demonstrated that the tool provided highly accurate predictions of antibiotic susceptibility to 31 agents [ 7 ]. Evaluation was extended to 781 MRSA genomes from 777 consecutive patients, which was compared with analytic outputs from a bespoke researcher-led informatics pipeline [ 8 ]. There was full concordance between the two analysis methods for species identification, detection of mec genes and multi-locus sequence type (ST) assignment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation